DCARES: Developmental Assessment & Reporting System for Special Need Children - Hamizi, Nurin Athirah; Kasim, Shahreen (Applied Information Technology And Computer Science, 2025)
Due to the challenges with manual, paper-based evaluation methods faced by LittleOnes Eduworld preschool, the Developmental Assessment & Reporting System for Special Need Children has been proposed. This web-based solution system was developed to overcome the challenges such as inefficiencies, data loss, disorganized data, and time-consuming assessment processes, which make it difficult for teachers to track children progress effectively. The system is developed using the Agile scrum methodology, and built with the Laravel framework, a PHP-based framework commonly used for developing large-scale application systems. Furthermore, it is designed to improve efficiency in completing children with inclusive program daily assessments, secured to manage educational data, user’s information and reduce administrative workloads. However, limitations such as dependency on internet access, browser compatibility issues, and limited analytics exist, present valuable opportunities for future enhancement. Hence, future enhancement, it is expected to be integrated into a mobile application and applying machine learning for prediction learning progress.